Carbonate storm deposits and C, O isotopes of the Lagoa do Jacaré Formation (Ediacaran) in the Paraopeba area, Bambuí Group, Brazil - Marcio Vinicius Santana Dantas; Alexandre Uhlein; Gabriel Jubé Uhlein; Alex Rodrigues de Freitas; Thaís Keuffer Mendonça; José Arthur Oliveira Santos; Samuel Amaral Moura Silva (Brazilian Journal of Geology, 2022)
Abstract A section investigated in the region of Paraopeba, Minas Gerais, provided detailed sedimentologic, stratigraphic and chemostratigraphic data from the Ediacaran Lagoa do Jacaré Formation, Bambuí Group, Southeast Brazil. This information allowed interpretation of tempestite facies in transgressive-regressive cycles, reinforcing the previously proposed storm-influenced sedimentation model and clarifying how it is associated with unusually high C-isotope values related to the Middle Bambuí Excursion (MIBE). Facies analysis of nine lithofacies identified at the GMD quarry based on field and petrographic descriptions showed distal tempestite facies grading upwards to a shallower, oncoidal/ooidal carbonate marine environment, then to basinal shales. The entire succession comprises a low-order transgressive hemicycle, recording the transition from a storm-influenced carbonate ramp to a siliciclastic-dominated platform. Chemostratigraphic data yielded high δ¹³C values ranging between +11.11‰ and +13.94‰. Our data contribute to the revision of the previously proposed interpretation and as well as to the understanding of paleoenvironmental conditions and C isotope signatures across the MIBE, near the Ediacaran-Cambrian boundary in the Bambuí Basin.